The Ethics of Utilitarianism in a Circular Economy - Martinus Tukiran; Tirtahadi Candra; Hendri Kornelius (Jurnal Filsafat "WISDOM", 2023)
In business competition, companies are required to be superior in creating added value for the products and services produced. However, within the limited availability of resources, companies must act wisely in managing business and achieving sustainable business objectives. This paper explains how a businessman can build their business by paying attention to morals. Ethical utilitarianism is an ethical view that emphasizes the goal of maximizing welfare for as many people as possible associated with the circular economy concept. A circular economy is an economic system that focuses on the efficient and responsible use of resources through the recycling, use, and renewal of resources. The study results show that ethical utilitarianism can be applied to circular economy principles and how these principles can bring significant economic and environmental benefits. This article also discusses some of the challenges and potential social injustices associated with implementing a circular economy and how to overcome them through a more inclusive approach.